2016
DOI: 10.1099/jgv.0.000609
|View full text |Cite
|
Sign up to set email alerts
|

A new eIF4E1 allele characterized by RNAseq data mining is associated with resistance to potato virus Y in tomato albeit with a low durability

Abstract: Allele mining on susceptibility factors offers opportunities to find new sources of resistance among crop wild relatives for breeding purposes. As a proof of concept, we used available RNAseq data to investigate polymorphisms among the four tomato genes encoding translation initiation factors [eIF4E1 and eIF4E2, eIFiso4E and the related gene new cap-binding protein(nCBP)] to look for new potential resistance alleles to potyviruses. By analysing polymorphism among RNAseq data obtained for 20 tomato accessions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Yet, evidence seems inconclusive. Additional elF4E1 alleles have been identified in wild tomato species, albeit with a limited resistance spectrum [81]. Conversely, in chili peppers (Capsicum annuum), many variants confer resistance and are thought to have originated from loci under positive selection.…”
Section: S Gene Diversitymentioning
confidence: 99%
“…Yet, evidence seems inconclusive. Additional elF4E1 alleles have been identified in wild tomato species, albeit with a limited resistance spectrum [81]. Conversely, in chili peppers (Capsicum annuum), many variants confer resistance and are thought to have originated from loci under positive selection.…”
Section: S Gene Diversitymentioning
confidence: 99%
“…Even if the exact mechanism(s) involved in eIF4E ‐mediated resistance are still unclear (Wang and Krishnaswamy, ), it has been shown that the viral genome linked protein (VPg) can interact with eIF4E, mimicking the 5’ cap structure of messenger RNAs (mRNAs). In addition, potyviruses can evolve towards resistance breaking through the acquisition of mutations that either restore compatibility of their VPg with the host mutant eIF4E or allow an interaction with another member of the eIF4E family (Charron et al , ; Gallois et al , , ; Lebaron et al , ; Takakura et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the eif4e1 KO eIF4E1 W69L plants' responses to both isolates were not homogenous, with seven plants showing full resistance and nine plants showing full susceptibility. This difference may be caused by resistance breaking, as previously shown for other eIF4E‐based alleles (Charron et al ., ; Lebaron et al ., ). On the contrary, both eif4e1 KO eIF4E1 T80DS81D and eif4e1 KO eIF4E1 N176K plants displayed full resistance to the No.…”
Section: Resultsmentioning
confidence: 97%
“…The independent selection of these mutations in pepper and in pea provides a compelling argument for their contribution to potyvirus resistance (Charron et al ., ). Interestingly, the G114R mutation located in Region II was not sufficient to provide efficient resistance, similar to equivalent mutations in the same region in the Solanum pimpinellifolium LA0411 resistance allele (Lebaron et al ., ). T80D‐S81D and G114R are substitutions that are frequently isolated in resistance alleles in pepper, tomato and pea, and appear to be under positive selection (Cavatorta et al ., ; Moury et al ., ).…”
Section: Discussionmentioning
confidence: 97%